EL MITO DE SAFO EN EL RELATO DECADENTE - De Diego, Rosa (Anales de Filología Francesa, 2007)
The homosexual woman, a reflection of a hermaphrodite mythical desire, is, during the end of the century, both a paradoxical and an obsessive literary figure. Sappho is, like the fatal woman, one of the protagonists, at the end of the century, who responds to a recurring misogyny in the imaginary creator. It deals with an artificial desire, éros intangible (Péladan 1910: 74), against nature, an impossible ideal: Sexe initial, sexe définitif absolu de l’amour, absolu de la forma, sexe qui nies le sexe, sexe d’éternité! Los à toi, Androgyne! (Péladan 1910: 76). Sappho, archetypical, androgynous figure, definitively constitutes the symbol of the abolition of sexes, of the confusion of genders, of the crisis of the traditional couple. She shows our fears and unsatisfied desires up.